The Issue of Arms and Its impact on British-American Influence in Iraq 1945-1957 - Jasim Hammadi, Ghaffar Jabbar (Journal of Tikrit University for Humanities, 2020)
The contemporary history of Iraq has witnessed many incidents that have had a significant impact on the instability of the state of the country's politics. These incidents are occupation of Britain of Iraq during the years of the First World War (1914-1918), and control the destiny of this country in all ways and means, prompting other foreign countries to walk on Britain through, especially after the discovery of oil in Iraq. The researcher tried to shed the light upon the interference of the United States and the basis of the political, economic and cultural ambitions in the internal affairs of Iraq. There was a competition between US and Britain to have the greatest influence, and as it is known, there are many studies and researches investigating how the British interests in Iraq were established and the methods used by Britain to penetrate in the internal affairs of Iraq. Also, the research studies similar interest of the US presence in Iraq especially in the period following World War II in different fields especially the fields of armaments and military missions, and the economy, oil, culture, and education.